2020
DOI: 10.5539/ijms.v12n4p30
|View full text |Cite
|
Sign up to set email alerts
|

Brand Activism, the Relation and Impact on Consumer Perception: A Case Study on Nike Advertising

Abstract: Recently various brands have been promoting their products through social issues that consumers are engaging with, by moving from social corporate responsibility to leadership and harnessing the brands' power to inspire social and environmental problems and change. Whether brands are creating social leadership campaigns to raise profit margins, or because they simply care about the issues they discuss, several brands have been playing this role through their campaigns, as seen for example with brands l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…According to Mukherjee and Althuizen (2020), a public backlash might be desirable, as it makes the proponents of the cause notice the campaign and start supporting the brand. This might have been the effect that Nike’s Dream Crazy campaign created – despite receiving negative comments on social media, Nike’s sales and the stock price soared following the campaign (Eyada, 2020). As a possible explanation, the campaign and the following backlash created so much media coverage that similar visibility would have been impossible to reach otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mukherjee and Althuizen (2020), a public backlash might be desirable, as it makes the proponents of the cause notice the campaign and start supporting the brand. This might have been the effect that Nike’s Dream Crazy campaign created – despite receiving negative comments on social media, Nike’s sales and the stock price soared following the campaign (Eyada, 2020). As a possible explanation, the campaign and the following backlash created so much media coverage that similar visibility would have been impossible to reach otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The success of Nike can not be separated from its efforts made to advertise and market itself to the world. The company has establish a close relationship with consumers intellectually and emotionally to encourage them to trust the brand (Eyada, 2020). Moreover, Nike try to use social media and special marketing campaigns to reach new audience and interact with them more directly.…”
Section: Superior Marketing Capabilitiesmentioning
confidence: 99%
“…Images were posted showing customers destroying Nike products. However despite a perceived negative response, financial analysts at Bloomberg reported that ten days after the campaign launch, Nike reached its all-time high on the stock market and increased value by $6bn (Eyada, 2020).…”
Section: Introductionmentioning
confidence: 99%